Assessment of yield stability in sugarcane genotypes using non-parametric methods (2015)
The evaluation of performance stability and high yields is essential for yield trials in different environments. This study was carried out to identifysugarcane genotypesthat have both a high mean cane yield, mesured in tons of cane per hectare (TCH), and stability across seven different environments, using 11 non-parametric statistical methods: Si(1), Si(2), Si(3), Si(6), NPI(1), NPI(2), NPI(3), NPI(4), RS, TOP and DE. The data came from acane yield of 20 genotypes, as measured at seven locations over three crop-years in the sugarcane regional trials of the Instituto Nacional de Investigaciones Agrícolas (INIA) of Venezuela. The genotypes V99-213, V99-236 and V00-50 showed promising yields and stability according to all of the non-parametric statistics. The TCH presented a positive association with the TOP, NPI(2), NPI(3) and Si(6) statistics. The analysis distinguished two groups of statistics using a principal component analysis (PCA). The first group (G1) was composed of the TOP, NPI(4), NPI(2), NPI(3), Si(3) and Si(6) statistics, which were located under the concept of dynamic or agronomic stability because they are associated with yield. The other group (G2) was composed of the NPI(1), Si(1), Si(2), DE and RS statistics, which fell within the static or biological stability concept.